Ulcerated Radiodermatitis Induced after Fluoroscopically Guided Stent Implantation Angioplasty - Maira Elizabeth Herz-Ruelas; Minerva Gómez-Flores; Joaquín Moxica-del Angel; Ivett Miranda-Maldonado; Ilse Marilú Gutiérrez-Villarreal; Guillermo Antonio Guerrero-González; Adriana Orelia Villarreal-Rodríguez (Hindawi Limited, 2014)
Cases of radiation-induced skin injury after fluoroscopically guided procedures have been reported since 1996, though the majority of them have been published in Radiology and Cardiology literature, less frequently in Dermatology journals. Chronic radiation dermatitis induced by fluoroscopy can be difficult to diagnose; a high grade of suspicion is required. We report a case of an obese 46-year-old man with hypertension, dyslipidemia, and severe coronary artery disease. He developed a pruritic and painful atrophic ulcerated skin plaque over his left scapula, six months after fluoroscopically guided stent implantation angioplasty. The diagnosis of radiodermatitis was confirmed histologically. We report this case to emphasize the importance of recognizing fluoroscopy as a cause of radiation dermatitis. A good clinical follow-up at regular intervals is important after long and complicated procedures, since the most prevalent factor for injury is long exposure time.